2016
DOI: 10.1002/ldr.2510
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling Effects of Using Coal Fly‐Ash and Bio‐Inoculant for Rehabilitation of Disturbed Biocrusts in Active Sand Dunes

Abstract: Active wind‐borne sand dunes, which lead to covering of fertile soils and agricultural fields, are one of the main problems in desertified lands worldwide, and stabilizing them poses a significant challenge. Such sand dunes may be naturally stabilized by biocrusts (biological soil crusts). One of the main restraints of biocrust development is the typical lack of fine particles in sand dunes. A possible artificial source of fine particles is coal fly‐ash, which is the by‐product of power stations and comprises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…Rozenstein et al () found more rapid growth of cyanobacteria on fine sand fractions (<125 um) than on the coarser fractions. Zaady et al () confirmed these results when they demonstrated greater growth of biocrusts when the inoculum was combined with coal fly ash. Likewise, Felde et al () showed that silt and clay content are the primary cementing agents responsible for stabilization of biocrusts in the Israeli Negev Desert.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Rozenstein et al () found more rapid growth of cyanobacteria on fine sand fractions (<125 um) than on the coarser fractions. Zaady et al () confirmed these results when they demonstrated greater growth of biocrusts when the inoculum was combined with coal fly ash. Likewise, Felde et al () showed that silt and clay content are the primary cementing agents responsible for stabilization of biocrusts in the Israeli Negev Desert.…”
Section: Discussionmentioning
confidence: 80%
“…We tested gypsum as an amendment because: (1) it has long been observed that gypsum soils support well‐developed lichen and moss communities (Martínez et al ); (2) recovery of biocrusts occurs more rapidly on finer‐textured soils (Belnap & Eldridge ; Rozenstein et al ; Felde et al ; Zaady et al ); and (3) gypsum forms a very stable soil surface. As with the other treatments, we did not observe any effect of gypsum on soil stability metrics or chlorophyll a concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on their application for biofertilizing and bioconditioning degraded arid soils are relatively few. Experiments under laboratory (Maqubela et al, 2009(Maqubela et al, , 2012Mugnai et al, 2018) and outdoor conditions (Wang et al, 2009;Wu et al, 2013;Lan et al, 2017;Park et al, 2017;Zaady et al, 2017) point to positive results in terms of soil stability and fertility.…”
Section: Introductionmentioning
confidence: 90%
“…Soil texture is one of the soil properties described as a key driver affecting cyanobacterial colonization in natural (Williams, Buck, Soukup, & Merkler, ) and artificial biocrusts (Rozenstein et al, ). However, while a large body of literature has addressed the application of cyanobacteria for restoring biocrust functioning on sandy soils (Chen et al, ; Park, Li, Zhao, Jia, & Hur, ; Wang, Liu, Li, Hu, & Rao, ; Wu et al, ; Xie, Liu, Hu, Chen, & Li, ; Zaady et al, ), only a few researchers have focused on biocrust rehabilitation experiments involving fine‐textured soils (Ayuso, Silva, Nelson, Barger, & Garcia‐Pichel, ; Falchini, Sparvoli, & Tomaselli, ; Maqubela, Muchaonyerwa, & Mnkeni, ; Rogers & Burns, ). In addition, differences in soil conditions, such as different degrees of degradation or physicochemical properties might cause different responses to cyanobacterial application.…”
Section: Introductionmentioning
confidence: 99%